Feeding of adult sea bream Brama japonica in the Pacific Ocean and the Bering Sea - Alexander Ya. Efimkin (Известия ТИНРО, 2014)
Feeding habits of adult sea bream are considered on the samples collected in the North Pacific and Bering Sea in the last several years. This species is a predator with the diet highly dependent on its habitat and composition of prey (small-sized fish and squids). It has two or three peaks of consumption daily, which change seasonally and year-to-year; anyway, the morning (3-6 a.m.) is usually the time of the lowest consumption, at least in summer and autumn, and the daytime is the normal time for feeding. The sea bream does not eat zooplankton usually, but Euphausia pacifica was a significant portion of its diet (34 %) in the southern part of surveyed area in the summer of 2009, possibly because of high concentrations of euphausiids in that area. Daily ration of adult sea bream is 2.5-3.5 % of its body weight.